Quantitation of malondialdehyde in gingival crevicular fluid by a high-performance liquid chromatography-based method - Bastos, Alliny Souza [UNESP]; de Melo Loureiro, Ana Paula; de Oliveira, Tiago Franco; Tfaile Corbi, Samia Cruz [UNESP]; Scarel Caminaga, Raquel Mantuaneli [UNESP]; Rossa Júnior, Carlos [UNESP]; Orrico, Silvana Regina Perez [UNESP] (Academic Press Inc. Elsevier B.V., 2012)
Lipid peroxidation (LPO) has been associated with periodontal disease, and the evaluation of malondialdehyde (MDA) in the gingival crevicular fluid (GCF), an inflammatory exudate from the surrounding tissue of the periodontium, may be useful to clarify the role of LPO in the pathogenesis of periodontal disease. We describe the validation of a method to measure MDA in the GCF using high-performance liquid chromatography. MDA calibration curves were prepared with phosphate-buffered solution spiked with increasing known concentrations of MDA. Healthy and diseased GCF samples were collected from the same patient to avoid interindividual variability. MDA response was linear in the range measured, and excellent agreement was observed between added and detected concentrations of MDA. Samples' intra- and interday coefficients of variation were below 6.3% and 12.4%, respectively. The limit of quantitation (signal/noise = 5) was 0.03 mu M. When the validated method was applied to the GCF, excellent agreement was observed in the MDA quantitation from healthy and diseased sites, and diseased sites presented more MDA than healthy sites (P < 0.05). In this study, a validated method for MDA quantitation in GCF was established with satisfactory sensitivity, precision, and accuracy. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Lipid peroxidation; Malondialdehyde; Periodontal diseases; Gingival crevicular fluid; HPLC